Recuperación de áreas deforestadas mediante la siembra con combinaciónespacial de especies forestales y frutales en el eje de carretera Iquitos - Nauta - 2021 - Rodriguez Rios, Cristina Carolina (2022)
This study was carried out in Iquitos - Nauta highway, San Juan Bautista district, in Mrs. Yolanda’s Pinedo Bartra plot, which purpose was to recover deforested areas by sowing with spatial combination of forest and agricultural species in Iquitos - Nauta highway. From the obtained results, 289 individuals of 8 different species were sown, such as screw, bolaina, capirona, marupa, añallu caspi, palo rosa, castaña and caoba; These species were planted in strips under the three bolillos system with tropical fruit species, such as uvilla, copoazu and umari. The forest species with the highest annual growth were bolaina and capirona with 54,6 cm and 41,7 cm. The fruit species with the highest annual growth were uvilla and umari with 26,63 cm and 21,97 cm. The percentage of mortality in all forest species on average was 22,15% while survival was 77,85 % with the GOOD category. The percentage of mortality in all fruit species on average was 27,08% while survival was 72,92% with the GOOD category. The forest species with the best survival result was the screw, the survival was 100%, followed by the marupa with 84,21 % of survival considered in the VERY GOOD category. The fruit species with the best survival results was the copoazu and the uvilla with 84,38% considered in the VERY GOOD category.